Avaliação do efeito da Citrullus Lanatus (melancia) e análise Da influência de polimorfismos genéticos em adultos Dislipidêmicos - Massa, Nayara Moreira (2013)
Dyslipidemia and genetic polymorphisms are associated with increased risk for developing cardiovascular diseases and watermelon appears to possess the potential to improve hyperlipidemia due to the presence of nutrients such as arginine and citrulline. We investigated the hypolipidemic effect of the extract of watermelon and influence of genotype of methylenetetrahydrofolate reductase (MTHFR C677T) and apolipoprotein E in response to supplementation. We developed an experimental, clinical phase II, randomized, double blind placebo controlled. Initially biochemical tests were performed to evaluate the lipid profile with 92 employees of a public institution, randomly. Of these, forty-three subjects diagnosed with dyslipidemia were randomly divided into two groups, the experimental (n = 22) and control (n = 21). The subjects were supplemented daily (6 g) for 42 days with extract of watermelon or a mixture of carbohydrates (sucrose / glucose / fructose). We evaluated anthropometric parameters (weight, body mass index, waist circumference and waist-hip ratio), biochemical (lipid profile), systemic arterial pressure and cardiac autonomic activity. The use of the extract of watermelon reduced plasma total cholesterol (p <0.05) and low density lipoprotein (p <0.01) without modifying values triglyceride, high density lipoprotein and very low density lipoprotein in human adults with dyslipidemia, pre hypertensive, overweight and glucose levels close to the upper limit. T allele carriers (C677T) in the experimental group apresentarm reduction of low density lipoprotein (p <0.01), longer allele C did not reduce the levels of this variable. The subjects in the experimental group and control had stimulated the sympathetic system, without modifications after supplementation in both groups. Beneficial effect of the extract on blood pressure levels, significantly reducing systolic blood pressure (p <0.01) and diastolic (p <0.01) in the experimental group, no significant changes in the control group. There were no changes in anthropometric parameters in both groups after supplementation with the extract of watermelon. In summary, the present study first demonstrated the beneficial effect of the consumption of watermelon extract in reducing plasma levels of lipids and systolic and diastolic blood pressure in humans, where MTHFR C677T polymorphism did not influence the levels of plasma lipids, but makes individuals more responsive to treatment with watermelon. The consumption of functional food may be an alternative therapy in the adjuvant treatment of patients with dyslipidemia, causing health promotion and minimizing the development of risk factors for cardiovascular disease.